Stimulating Strategy High-order Thinking Skills in Early Childhood Education by Utilizing Traditional Games - Aisyah, Siti; Tatminingsih, Sri; Chandrawati, Titi; Novita, Dian (Program Studi Magister Pendidikan Anak Usia Dini, 2024)
The education system in the 21st century needs some transformation, particularly in terms of enhancing thinking skills. Traditional games that are well-designed can be an effective strategy for stimulating higher order thinking Skills (HOTS). This research aims to develop active and creative learning models by utilizing traditional games to stimulate HOTS in early childhood. The current study is included in the descriptive-qualitative research. Data was collected using offline and face-to-face interview techniques. 20 teachers took part in this research. The finding illustrates that HOTS can be stimulated from an early age with several conditions, including developing play and learning activities that are well managed, fun, and consider the interests of early childhood. Games that effectively stimulate HOTS such as Dolanan Gatheng, Bekel Ball, Tuk Tuk Geni, Gotah Games, Gundu, and Congklak. Children also need to carry out simple and fun science activities, so they are trained to think and act scientifically and systematically. There are several suggestions regarding opportunities for future research applications. This research only includes traditional games to stimulate HOTS. Other researchers may also consider other innovative methods or other kinds of games that are also effective for increasing HOTS in early childhood. Keywords: higher-order thinking skills, early childhood education, traditional games, active learning References: Adi, B. S., Irianto, D. P., & Sukarmin, Y. (2021). Teachers’ perspectives on motor learning with traditional game approach among early children. Jurnal Cakrawala Pendidikan, 41(1). https://doi.org/10.21831/cp.v41i1.3684 Alizadeh, F., Hashim, M. N., & Amini, R. (2014). Place of teahouse in performance of traditional plays on Iran. 5th International Conference on Humanities, Geography and Economics, 8–10. https://www.academia.edu/27519965/Place_of_Teahouse_in_Performance_of_Traditional_Plays Anggraini, N. P., Budiyono, & Pratiwi, H. (2019). Analysis of higher order thinking skills students at junior high school in Surakarta. Journal of Physics: Conference Series, 1211(1). https://doi.org/10.1088/1742-6596/1211/1/012077 Asari, S., Husniah, R., Ma’rifah, U., & Anwar, K. (2019). Fostering Students’ High Order Thinking Skills through the Use of Interpretation Cards. International Journal of Education and Literacy Studies, 7(4), 17. https://doi.org/10.7575/aiac.ijels.v.7n.4p.17 Astini, B. N., Rachmayani, I., & Zakiyah, N. F. (2022). Identifikasi permainan tradisional untuk meningkatkan perkembangan anak usia dini di kabupaten lombok utara. Jurnal Pendidikan Anak, 11. Aulia, R., & Ngaisah, N. C. (2023). Peran Pendidikan Anak Usia Dini dalam Fungsi Sosialisasi Keluarga di Kelurahan Teluk Merarti. Bunayya: Jurnal Pendidikan Anak, 49–62 Batsaikhan, J., & Kaye, C. (2017). Horse Racing With Sheep Ankle Bones: The Play of Nomadic Children in Mongolia. Journal of Childhood Studies, 42(3), 40. https://doi.org/10.18357/jcs.v42i3.17893 Choi, M.-J., & Sohng, K.-Y. (2018). The Effect of the Intergenerational Exchange Program for Older Adults and Young Children in the Community Using the Traditional Play. Journal of Korean Academy of Nursing, 48(6), 743. https://doi.org/10.4040/jkan.2018.48.6.743 Creswell, J. W. (2015). Educational research: Planning, conducting, and evaluating quantitative and qualitative research (Fifth edition). Pearson. Dima, M. L. B., Daflizar, D., & Ahmadi, A. (2021). The implementation of higher order thinking skills (hots) in english language teaching: The case of Indonesian Senior High School EFL teachers. Journal of English Language Teaching, 8(2), 255–268. https://doi.org/https://doi.org/10.26858/eltww.v8i2.20468 Driana, E., & Ernawati, E. (2019). Teachers’ Understanding And Practices In Assessing Higher Order Thinking Skills At Primary Schools. ACITYA Journal of Teaching & Education, 1(2), 110–118. https://doi.org/10.30650/ajte.v1i2.233 Ersan, Ş. (2017). Arranging play and learning environtment in early years classroom. In I. Koleva. & G. Duman (Ed.), Educational research and practice (pp. 54–64). Sofia: St. Kliment Ohridski University Press. https://www.researchgate.net/publication/322526425_Arranging_Play_And_Learning_Environments_In_Early_Years_Classroom Facione, N. C., & Facione, P. A. (1996). Externalizing the critical thinking in knowledge development and clinical judgment. Nursing Outlook, 44(3), 129–136. Feriver, Ş., Olgan, R., Teksöz, G., & Barth, M. (2019). Systems Thinking Skills of Preschool Children in Early Childhood Education Contexts from Turkey and Germany. Sustainability, 11(5), 1478. https://doi.org/10.3390/su11051478 FitzPatrick, B., & Schulz, H. (2015). Do Curriculum Outcomes and Assessment Activities in Science Encourage Higher Order Thinking? Canadian Journal of Science, Mathematics and Technology Education, 15(2), 136–154. https://doi.org/10.1080/14926156.2015.1014074 Gold, Z. S., Elicker, J., Choi, J. Y., Anderson, T., & Brophy, S. P. (2015). Preschoolers’ Engineering Play Behaviors: Differences in Gender and Play Context. Children, Youth and Environments, 25(3), 1. https://doi.org/10.7721/chilyoutenvi.25.3.0001 Hamdan, A. (2020). Early childhood teachers’ skills in the twenty-first century: A Predictive Study. IUG Journal of Educational and Psychology Sciences, 6, 546–572. https://www.researchgate.net/publication/349604848 Harnadek, A. (2010). Critical Thinking Book Two. California: Midwest Pub. Hashemi, M. R., & Ghanizadeh, A. (2012). Critical discourse analysis and critical thinking: An experimental study in an EFL context. System, 40(1), 37–47. https://doi.org/10.1016/j.system.2012.01.009 Hastiana, D., & Daliman, D. (2023). Perkembangan Kognitif Usia Pra Operasional dalam Berbagai Perspektif Permainan Tradisional. JIIP - Jurnal Ilmiah Ilmu Pendidikan, 6(6), 4136–4141. https://doi.org/10.54371/jiip.v6i6.1750 Heong, Y. M., Othman, W. B., Yunos, J. B. M., Kiong, T. T., Hassan, R. Bin, & Mohamad, M. M. B. (2011). The Level of Marzano Higher Order Thinking Skillsamong Technical Education Students. International Journal of Social Science and Humanity, 121–125. https://doi.org/10.7763/IJSSH.2011.V1.20 Iswinarti, I., & Suminar, D. R. (2019). Improving Children’s Problem-Solving Skills Through Javanese Traditional Games. Jurnal Cakrawala Pendidikan, 38(3), 578–589. https://doi.org/10.21831/cp.v38i3.25331 JDIH BPK RI. (2003, July 8). UU No. 20 Tahun 2003 tentang Sistem Pendidikan Nasional. https://peraturan.bpk.go.id/Home/Details/43920/uu-no-20-tahun-2003 Kamid, K., Rohati, R., Rahmalisa, Y., Anggo, M., Septi, S. E., Azzahra, M. Z., & Nawahdani, A. M. (2021). Engklek Game in mathematics: How difference and relationship student attitude towards science process skills? Cypriot Journal of Educational Sciences, 16(6), 3109–3123. https://doi.org/10.18844/cjes.v16i6.6500 Kim, M.-S., & Choi, J.-A. (2015). The Effects of a 『Traditional Play Program』 on a Child’s Self-Esteem and Social Competency in a Community Child Center. Korean Journal of Child Studies, 36(6), 39–57. https://doi.org/10.5723/KJCS.2015.36.6.39 Kosasih, A., Supriyadi, T., Firmansyah, M. I., & Rahminawati, N. (2022). Higher-Order Thinking Skills in Primary School: Teachers’ Perceptions of Islamic Education. Journal of Ethnic and Cultural Studies, 9(1), 56–76. https://doi.org/10.29333/ejecs/994 Krathwohl, D. R. (2002). A Revision of Bloom’s Taxonomy: An Overview. Theory Into Practice, 41(4), 212–218. https://doi.org/https://doi.org/10.1207/s15430421tip4104_2 Melianasari, H., & Suparno, S. (2018). The Importance of Traditional Games to Improve Children’s Interpersonal Skill. Proceedings of the 4th International Conference on Early Childhood Education. Semarang Early Childhood Research and Education Talks (SECRET 2018). Proceedings of the 4th International Conference on Early Childhood Education. Semarang Early Childhood Research and Education Talks (SECRET 2018), Semarang, Indonesia. https://doi.org/10.2991/secret-18.2018.29 Moon, J. (2007). Critical thinking: An exploration of theory and practice. In London: Routledge Falmer. https://eric.ed.gov/?q=21&pg=85&id=EJ984914 Preus, B. (2012). Authentic instruction for 21st century learning: Higher order thinking in an inclusive school. American Secondary Education, 40(3), 59–79. https://eric.ed.gov/?q=21&pg=85&id=EJ984914 Qasrawi, R., & Beniabdelrahman, A. (2020). The Higher And Lower-Order Thinking Skills (Hots And Lots) In Unlock English Textbooks (1st And 2nd Editions) Based On Bloom’s Taxonomy: An Analysis Study. In International Online Journal of Education and Teaching (IOJET) (Vol. 7, Issue 3). https://iojet.org/index.php/IOJET/article/view/866 Resnick, L. B. (1987). Education and learning to think. http://faculty.wiu.edu/JR-Olsen/wiu/common-core/precursor-documents/PersonalUseOnlyEducation and Learning to Think.pdf Roza, D., Nurhafizah, N., & Yaswinda, Y. (2019). Urgensi Profesionalisme Guru Pendidikan Anak Usia Dini dalam Penyelenggaraan Perlindungan Anak. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 4(1), 277. https://doi.org/10.31004/obsesi.v4i1.325 Sarana, N. V. (2019). The Bildungsdrama and Alexander Ostrovsky’s Plays. Russia: De Gruyter. Slamet, Y. (2020). Upaya Guru Dalam Meningkatkan Kemampuan Motorik Kasar Melalui Permainan Tradisional Egrang Batok Pada Anak Usia Dini (PAUD Melati 4 Jakarta Pusat). SKripsi, Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, IPTIA, Jakarta. Sujiono, Y. N. (2013). Konsep dasar pendidikan anak usia dini. PT Indeks. Suprapto, E., Fahrizal, F., Priyono, P., & K., B. (2017). The Application of Problem-Based Learning Strategy to Increase High Order Thinking Skills of Senior Vocational School Students. International Education Studies, 10(6), 123. https://doi.org/10.5539/ies.v10n6p123 Tatminingsih, S. (2019). Coloured Stick: Teaching With A Comprehensive Game For Improving Children’s Social-Emotional Ability In Kindergarten. Különleges Bánásmód - Interdiszciplináris Folyóirat, 5(1), 59–65. https://doi.org/10.18458/KB.2019.1.59 Tatminingsih, S. (2020). Perception of kindergarten teachers on the utilization of traditional games in learning in West Nusa Tenggara, Indonesia. In Emerging Perspectives and Trends in Innovative Technology for Quality Education 4.0 (pp. 19–22). Routledge. https://doi.org/10.1201/9780429289989-6 Thomas, A., & Thorne, G. (2010). How to increase higher order thinking. https://www.semanticscholar.org/paper/How-to-Increase-Higher-Order-Thinking-Thomas-Thorne/e1ac293c0dd2aeb6f1d61ed17fde3547cd483bcc UNESCO. (2023). Why early childhood care and education matters. https://www.unesco.org/en/articles/why-early-childhood-care-and-education-matters. Waller, T., Ärlemalm-Hagsér, E., Sandseter, E. B. H., Lee-Hammond, L., Lekies, K., & Wyver, S. (2017). The SAGE Handbook of Outdoor Play and Learning. SAGE Publications Limited.